A dynamical-systems approach to the evolution of morphonotactic and lexical consonant clusters in English and Polish - Baumann, Andreas; Kaźmierski, Kamil (Yearbook of the Poznan Linguistic Meeting, 2016)
Consonant clusters appear either lexically within morphemes or morphonotactically across morpheme boundaries. According to extant theories, their diachronic dynamics are suggested to be determined by analogical effects on the one hand as well as by their morphological signaling function on the other hand. This paper presents a mathematical model which allows for an investigation of the interaction of these two forces and the resulting diachronic dynamics. The model is tested against synchronic and diachronic language data. It is shown that the evolutionary dynamics of the cluster inventory crucially depend on how the signaling function of morphonotactic clusters is compromised by the presence of lexical items containing their morpheme internal counterparts.